Severe left anterior descending artery stenosis with proximal arteriovenous malformation presenting as acute myocardial infarction - Maskon, Oteh; NMA, Hanim; S, Noorfaizan; Mohd Shah, Azarisman Shah (Singapore Medical Association, 2009)
Congenital coronary artery anomalies are rare, with an incidence of about 0.06–1.3 percent of all patients undergoing cardiac catheterisation. They are commonly asymptomatic, but potentially serious lesions may lead to myocardial ischaemia, infarction and/or sudden cardiac death. The occurrence of a concomitant stenotic lesion is exceedingly rare. We report an 80-year-old man who presented with acute anterior myocardial infarction. Coronary angiography revealed severe proximal left anterior descending (LAD) and arteriovenous malformation (AVM) from the first septal branch of the LAD. The LAD stenosis and the AVM were successfully treated with two Jomed® covered stents.